Ankle-Brachial Index for Risk Stratification in Patients With Symptomatic Peripheral Artery Disease With and Without Prior Lower Extremity Revascularization: Observations From the EUCLID Trial. (13th July 2021) - Hiatt, William R.; Hess, Connie N.; Bonaca, Marc P.; Kavanagh, Sarah; Patel, Manesh R.; Baumgartner, Iris; Berger, Jeffrey S.; Blomster, Juuso I.; Jones, W. Schuyler; Katona, Brian G.; Mahaffey, Kenneth W.; Norgren, Lars; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: A reduced ankle-brachial index (ABI) is a measure of atherosclerosis and is associated with ischemic risk in the general population. Whether this relationship is maintained in peripheral artery disease after lower extremity revascularization (LER), which can modify ABI, is unknown. Methods: The EUCLID (Examining Use of Ticagrelor in Peripheral Artery Disease) enrolled 13 885 patients with symptomatic peripheral artery disease; 57% with prior LER, and 43% with ABI ≤0.80. The primary major adverse cardiovascular events (MACE) outcome was a composite of cardiovascular death, myocardial infarction, or ischemic stroke. Major adverse limb events (MALE) included acute limb ischemia and major amputation. An adjusted Cox proportional hazards model demonstrated a nonlinear relationship between ABI and outcomes. A restricted cubic spline model with 4 knots was developed to identify the best fitting model to describe the relationship between ABI and MACE and MALE risk. Results: Baseline ABI (mean±SD) was 0.77±0.21 in participants with prior LER and 0.63±0.14 in those without prior LER ( P <0.0001). There was no statistical interaction between prior LER and ABI, meaning the shapes of the cubic spline models were similar between groups. In those with prior LER, for every 0.10 unit lower ABI below an ABI of 1.00, the hazard ratio for MACE was 1.08 (95% CI, 1.04–1.12; P <0.0001), below an ABI of 0.80 the hazard ratio for MALE was 1.32 (95% CI, 1.21–1.43; P <0.0001). In patients without prior LER, every 0.10 unit lower ABI below an ABI of 0.70 was associated with increased risk for MACE (hazard ratio, 1.14 [95% CI, 1.06–1.23]; P =0.0004) and MALE (hazard ratio, 1.27 [95% CI, 1.08–1.49]; P =0.003). Conclusions: Patients with established peripheral artery disease, particularly those with prior LER, have an increased risk of MACE and MALE. The ABI remains a strong predictor of MACE and MALE ischemic events with an inverse relationship below an ABI threshold for patients with and without prior LER. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01732822.